Artificial Intelligence : Ethical, social, and security impacts for the present and the future - Mehan, Julie (IT Governance Publishing Ltd., 2024)
A global perspective on AI The rise of AI and super-intelligent AI raises ethical issues. AI is the power behind Google's search engine, enables social media sites to serve up targeted advertising, gives Alexa and Siri their voices, and enables OpenAI's ChatGPT to produce written responses from just a few prompts by the user. It is also the technology enabling self-driving vehicles, predictive policing, and autonomous weapons that can kill without direct human intervention. All of these bring up complex ethical issues that are still unresolved and will continue to be the subject of ongoing debate.   This book: Explores the complex topic of AI ethics in a cross-functional way; Enables understanding of the associated ethical challenges of AI technologies; Provides an up-to-date overview of the potential positive and negative outcomes of AI implementations; and Has been updated to reflect the ethical challenges of AI in 2024 and beyond, and the moral imperative of navigating this new terrain. This book presents a concrete approach to identifying appropriate ethical principles in AI solutions